COMPARISON OF LEGAL LIABILITY OF HOSPITALS IN INDONESIA WITH ASEAN COUNTRIES - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Jurnal Kesehatan, 2025)
This research examines the comparative legal liability of hospitals in Indonesia with ASEAN countries. The analysis shows that there are significant differences in regulatory and supervisory frameworks between countries in the region. Indonesia still relies on a national regulatory system, whereas some countries such as Singapore and Malaysia use an international approach by involving independent accreditation bodies. Differences are also seen in the handling of malpractice cases and professional liability, where countries with more developed health insurance systems offer better protection for patients and institutions. The study concludes that Indonesia needs to strengthen accreditation standards and insurance coverage to improve the quality of care and competitiveness of its hospitals at the regional level.